An in-vitro study on effects of laser activation on dye penetration in human root dentin - Clara Isabel Anton y Otero; Laurine Marger; Enrico di Bella; Albert Feilzer; Ivo Krejci; Marwa Abdelaziz (Medical Journals Sweden, 2024)
Objective: To evaluate the penetration of a dye in root dentin after activation with different laser wavelengths. Materials: Palatal roots of 38 human molars were enlarged and disinfected. Irrigation activation was performed with an Er:YAG laser: @50 mJ, 15 Hz (Er:YAG); a 9.3 µm CO2 laser: @40% power (CO2); diode lasers 455 nm/970 nm: @0.8 W, 15 Hz (D455, D970) and 808/980 nm: @1 W (D808, D980) and compared to positive control: etching with 35% H3PO4 (POS); negative control: water (NEG) and conventional needle irrigation: NaOCl and ethylenediaminetetraacetic acid (EDTA) (CONV). Methylene blue solution was introduced in the canal and laser-activated or left untouched for 100 s before the roots were dried and cut into horizontal slices. Dye penetration was automatically calculated by color recognition of two samples per root third (n = 8 per group in each coronal, middle and apical root thirds). The presence and absence of a smear layer was checked in two additional samples of the negative and positive control under scanning electron microscopy (SEM).  Results: Full-depth infiltration was not achieved in any group. Dye penetration in CONV was significantly less than in Er:YAG, CO2, POS, D455, D970, D808 and similar to NEG and D980 when results of different root thirds were pooled. Conclusion: Laser activation using certain parameters enhanced dye penetration compared to conventional needle irrigation with NaOCl and EDTA (CONV).